2023
DOI: 10.3390/ijms24087128
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Contribution in Interactions between Turnip mosaic virus and Arabidopsis thaliana Mutants Lacking Respiratory Burst Oxidase Homologs D and F

Abstract: Respiratory burst oxidase homologs (Rbohs) play crucial and diverse roles in plant tissue-mediated production of reactive oxygen species during the development, growth, and response of plants to abiotic and biotic stress. Many studies have demonstrated the contribution of RbohD and RbohF in stress signaling in pathogen response differentially modulating the immune response, but the potential role of the Rbohs-mediated response in plant–virus interactions remains unknown. The present study analyzed, for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 113 publications
6
24
0
Order By: Relevance
“…This increase correlated with a significant reduction in the amount and expression of PVY NTN and the induction of the HR response. A similar pattern of stable increase in levels of GSH and GSSG was observed in Arabidopsis mutant plants with increased resistance ( rbohF ) and HR-like reaction ( rbohD/F ) infected by TuMV ( Otulak-Kozieł et al., 2023 ), which was also associated with decreased expression of the virus. Singh et al.…”
Section: Role Of Glutathione Cycle In Regulation Of Resistant Host-pl...supporting
confidence: 62%
See 3 more Smart Citations
“…This increase correlated with a significant reduction in the amount and expression of PVY NTN and the induction of the HR response. A similar pattern of stable increase in levels of GSH and GSSG was observed in Arabidopsis mutant plants with increased resistance ( rbohF ) and HR-like reaction ( rbohD/F ) infected by TuMV ( Otulak-Kozieł et al., 2023 ), which was also associated with decreased expression of the virus. Singh et al.…”
Section: Role Of Glutathione Cycle In Regulation Of Resistant Host-pl...supporting
confidence: 62%
“…(2022a) and Otulak-Kozieł et al. (2022b ; 2023) detected modulation of glutathione levels during investigations of infections caused by PVY NTN and TuMV on susceptible and resistant (with hypersensitive response or hypersensitive-like, HR or HR-like) respectively on potato and rbohF and rbohD/f mutants of Arabidopsis ( Figure 2 ). Resistant potato plants infected by PVY NTN exhibited a dynamic increase in the content of glutathione during both resistance and, to some extent, susceptible reactions.…”
Section: Role Of Glutathione Cycle In Regulation Of Resistant Host-pl...mentioning
confidence: 98%
See 2 more Smart Citations
“…It is reported that calcium-dependent protein kinase CPK5 contributes to priming, which could enhance basal resistance without the enhancement of SAR in an Arabidopsis sard1-1 mutant [29]. CPK5 is involved in RBOHD-mediated ROS signaling [30], and glutathione can act as a key signaling factor through redox homeostasis [31].…”
Section: Translation Regulation Is An Alternative Priming Effect Of N...mentioning
confidence: 99%